Android-Based Comics: An Alternative Media to Improve Scientific Literacy - Listianingsih, Mardianti; Astuti, Irnin Agustina Dwi; Dasmo, Dasmo; Bhakti, Yoga Budi (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
The students’ scientific literacy nowadays is relatively low because the lack of media learning to improve scientific literacy. This research aimed to test the feasibility of developed Android-based comics on material style and motion to scientific literacy. This study used a research and development using ADDIE (analysis, design, development, implementation, evaluation) model. The subject of this research is students from grade VIII at one of the junior high school in Indonesia. The instruments of this research are validation sheets and student response sheets. The result of validation test in term of material expert acquired on average percentages of 93.26% and media experts at 97.08%. Moreover, the pretest of students' scientific literacy is 2.26, and the post-test of students' scientific literacy is 3.40, with the N-gain formula obtained a value of 0.72 with the category